Improving Ustaz and Ustazah Communication Skills for Students at TPQ Rojaul Khoir Griya Mijen Permai Semarang - Firmansyah, Asep; Kasmuri, Kasmuri; Gunawan, Muhammad; Lijea, Isma Ae; Ahmed, Tanjeel (Prosperity: Journal of Society and Empowerment, 2024)
This research aims, firstly, to provide knowledge and understanding to ustaz and ustazah about the importance of communication while at the same time providing reinforcement on how to apply communication skills in the learning process to santri or students and secondly to find out the results of implementing the communication skills that teachers have in the learning process. The method used in this research is descriptive-analytical using a participatory approach. The research instrument used interviews. The subject of the activity is the teachers and the field of education. Activities to improve the communication skills of ustaz and ustazah for students of TPQ Rojaul Khoir, Mijen Semarang were carried out for four days and were attended by 40 participants consisting of teachers, prayer teachers in the field of education, and other managers. After carrying out a workshop to improve communication skills for ustaz and ustazah, the activity continued with evaluating and preparing a follow-up program using brainstorming. The importance of communication strategies taught by students at TPQ Rojaul Khoir to improve learning quality is a common concern, so communication skills should be part of implementing activity programs at TPQ Rojaul Khoir. After communication skills were implemented in learning activities, there was a change for the better; namely, the class was more controlled, and the learning process was more meaningful.